A Novel Option of Uninterrupted Closure of Surgical Wounds - Sulamanidze, Marlen A (Medknow Publications, 2009)
BACKGROUND: A cosmetically pleasing postoperative scar is an important aim of all aesthetic surgeries. Use of proper suture materials for delicate and gentle suturing of the operative injury is an important requirement for achieving satisfactory scars. However, closure of the edges of wounds by means of conventional suture materials does not always meet the requirements to achieve this objective. AIM: To simplify and facilitate the process of surgical wound closure, to improve the quality of scar, and to achieve a good cosmetic effect through the introduction of a new type of suture material. MATERIALS AND METHODS: We have introduced a new surgical suturing material—a nontraumatic, barbed thread connected with the suture needle—APTOS SUTURE (European patent 1075843 as of 1999). Presented herein is a new modification of the technique of uninterrupted subcutaneous and intracutaneous suturing of wound edges, and the details of our experience with this material. RESULTS: Our experience shows that, with use of APTOS, wound closure is carried out easily and quickly. The wound remains stable, the time of healing is shortened, and the process of suture removal is simplified, resulting in an aesthetically pleasing scar. CONCLUSIONS: The technique of surgical wound suturing proposed herein is a simple, facilitated, and efficient option of wound-edge closure, which can successfully be used, both in general and in aesthetic surgery for wound closure, such as plasty of scars, face lift, mammoplasty, and abdominal plasty.